ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN MOTOR LISTRIK PADA PT. UNGGUL ENERGI ENGINEERING – GRESIK - Deby putri meigiti; Rika Yuliastuti (Ekomania, 2023)
The achievement of sales targets that have been inaugurated previously and to identify efficient methods of marketing GESITS electric motorcycles and what policies are implemented by the industry. The truth in the research is a prediction that the sales target of the GESITS electric motorcycle has not been achieved, the competition continues to be fierce, with a credit sales system, the quality of goods does not match the types of consumers, and services. And the research variables are competition, sales system, product and service. In analyzing the information, the author suggests a descriptive method is that after information and action there are also theoretical concepts used in this information analysis related to sales, so that with credit or cash policies, prices, products, promotions and services can be expected if sales targets are not achieved. Motor Gesits at PT. Superior Energy Engineering can be overcome. Based on the results of research, it was found that the existence of a sales policy greatly influences consumers to buy. Inaugurated by the industry in credit sales, it is very helpful to increase sales.